Tobacco industry targeting youth in Argentina - Braun, S (2008)
BACKGROUND/AIM: Argentina has one of the highest cigarette smoking rates among both men and women in the Americas and no legislated restrictions on tobacco industry advertising. The tobacco industry has traditionally expanded markets by targeting adolescents and young adults. The objective of this study was to determine whether and how the tobacco industry promotes cigarettes to adolescents in Argentina. METHODS: We conducted a systematic search of tobacco industry documents available through the internet dated between 1995 and 2004 using standard search terms to identify marketing strategies in Argentina. A selected review of the four leading newspapers and nine magazines with reported high readership among adolescents was completed. The selected print media were searched for tobacco images and these were classified as advertisements if associated with a commercial product or as a story if not. RESULTS: The tobacco industry used market segmentation as a strategy to target Argentinean consumers. British American Tobacco (BAT) undertook a young adult psychographic study and classified them as “progressives”, “Jurassics” or “conservatives” and “crudos” or “spoiled brats”. BAT marketed Lucky Strike to the “progressives” using Hollywood movies as a vehicle. The tobacco industry also targeted their national brands to the conservatives and linked these brands with “nationalistic values” in advertising campaigns. Philip Morris promoted Marlboro by sponsoring activities directed at young people and they launched the 10 cigarettes packet as a starter vehicle. CONCLUSIONS: The tobacco industry used psychographic segmentation of the population and developed advertising strategies focused on youth. Tobacco control researchers and advocates must be able to address these strategies in counter-marketing interventions.